2001
DOI: 10.2174/1381612013397915
|View full text |Cite
|
Sign up to set email alerts
|

Current Therapies and Emerging Targets for the Treatment of Diabetes

Abstract: Concurrent with the spread of the western lifestyle, the prevalence of all types of diabetes is on the rise in the world's population. The number of diabetics is increasing by 4-5% per year with an estimated 40-45% of individual's over the age of 65 years having either type II diabetes or impaired glucose tolerance. Since the signs of diabetes are not immediately obvious, diagnosis can be preceded by an extended period of impaired glucose tolerance resulting in the prevalence of beta-cell dysfunction and macro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
90
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(92 citation statements)
references
References 136 publications
(147 reference statements)
1
90
0
1
Order By: Relevance
“…Fujita et al (1998) reported that intestinal glucose absorption through SGLT1 was increased in 6-week-old OLETF rats before the onset of insulin resistance and hyperinsulinemia. An SGLT1 inhibitor has been shown to counteract hyperglycemia and obesity (Wagman & Nuss 2001). In accordance with previous studies, this study also detected enhanced intestinal SGLT1 expression in db/db mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fujita et al (1998) reported that intestinal glucose absorption through SGLT1 was increased in 6-week-old OLETF rats before the onset of insulin resistance and hyperinsulinemia. An SGLT1 inhibitor has been shown to counteract hyperglycemia and obesity (Wagman & Nuss 2001). In accordance with previous studies, this study also detected enhanced intestinal SGLT1 expression in db/db mice.…”
Section: Discussionmentioning
confidence: 99%
“…This process could eventually potentiate the development of hyperglycemia and diabetes. Conversely, inhibitors of SGLT1 have been shown to counteract obesity (Wagman & Nuss 2001).…”
Section: Introductionmentioning
confidence: 99%
“…3 Although several drugs are in clinical use for symptomatic treatment of T2DM, 4,5 these therapies are inadequate for 30-40% of the patients. 6 Among several investigational fields to diminish hepatic glucose output in T2DM, glycogen phosphorylase (GP) as a main regulatory enzyme of glycogen metabolism has become a validated 50 target. 2 Protein crystallographic studies have shown that endogenous and synthetic modulators can bind to six major sites in GP: the catalytic, the inhibitor, the allosteric (or AMP-binding), the glycogen storage, and the new allosteric sites, 7 as well as the newly discovered benzimidazole site.…”
mentioning
confidence: 99%
“…Since it has been suggested that compounds that reduce protein tyrosine phosphatase 1B (PTP1B) activity or expression levels can used for the treatment of either type 2 diabetes or obesity, [1][2][3][4][5] there have been found a number of natural products reported to possess suppressive effects on PTP1B enzyme in our program searching for anti-diabetes agents from nature. [6][7][8][9][10][11][12][13][14][15][16] Previously, we found that an EtOAcsoluble extract of the root bark of Erythrina mildbraedii exhibited inhibitory effect on PTP1B activity and demonstrated that prenylated flavonoids are principles of this extract.…”
mentioning
confidence: 99%